Weighted Multi Criteria of Consultant and Contractor Selection at PT. JICT - Dewi, Lulita Indra; Firman, Aries F (The Indonesian Journal of Business Administration, 2012)
The study aims to improve the tender evaluation, particularly in selection criteria. The criteria and attributes were gathered from current procedures and other companies as a benchmark, and also selected some others from 40 attributes introduced by Ling which were suitable with the company’s condition being researched. Later on, a survey using a questionnaire was distributed to project owners and consultant’s employees as the respondents using the Likert scale method to assess the performance level of the vendors in delivering service and level of importance for each criterion and attribute. By using MAVT (multi-attribute value technique), the weights were calculated. Meanwhile, the bid proposal was rated with a standard ratings scale. A formula that showed the relation between the weights and rating was created. This formula proposed the total aggregate score for the technical evaluation. And by summarizing aggregate scores with the bid price score, the highest-scored bidder would be awarded. Another factor discovered in this research was the importance of leadership to manage the team and resources well during delivering a great service for the project owner. Keywords:    project management, criteria, attribute, weights, rating, aggregate score, and leadership.